2013
DOI: 10.1016/j.riob.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Underestimating our influence over others at work

Abstract: Employees at all organizational levels have influence over their subordinates, their colleagues, and even their bosses. But are they aware of this influence? We present evidence suggesting that employees are constrained by cognitive biases that lead them to underestimate their influence over others in the workplace. As a result of this underestimation of influence, employees may be reluctant to spearhead organizational change, discount their own role in subordinates' performance failures, and fail to speak up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 142 publications
(125 reference statements)
2
13
1
Order By: Relevance
“…As such, this study establishes an emotional dual‐process mechanism that is dependent on the type of self‐conscious moral emotion. Our findings also contribute to the literature stating that other‐oriented (i.e., guilt) and self‐concerned (i.e., shame) emotions can co‐occur and need to be captured simultaneously to be able to accurately predict subsequent behavioural strategies (Bohns & Flynn, ; de Dreu & Nauta, ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As such, this study establishes an emotional dual‐process mechanism that is dependent on the type of self‐conscious moral emotion. Our findings also contribute to the literature stating that other‐oriented (i.e., guilt) and self‐concerned (i.e., shame) emotions can co‐occur and need to be captured simultaneously to be able to accurately predict subsequent behavioural strategies (Bohns & Flynn, ; de Dreu & Nauta, ).…”
Section: Discussionsupporting
confidence: 64%
“…Accordingly, the closer knowledge hiding perpetrators feel to the knowledge hiding target, the stronger their negative emotional reactions may be. Contextual factors refer to a set of external cues from which organizational members deduce what their attitudes and behaviour should be (Bohns & Flynn, 2013;Salancik & Pfeffer, 1978). For example, contextual factors that increase employees' awareness about their moral wrongdoing, such as ethical climates (Victor & Cullen, 1988), corporate ethical codes (Stevens, 2008), and ethical supervisors (Brown & Treviño, 2006;Treviño, Brown, & Hartman, 2016), may strengthen the link between knowledge hiding and self-conscious moral emotions.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…There are numerous other potential moderators of the underestimation-of-compliance effect (for additional possibilities, see Bohns & Flynn, 2013). One factor of interest is gender (Eagly, 1983); however, we have found no reliable gender effects in our studies.…”
Section: Other Factorscontrasting
confidence: 59%
“…Sherif's (1935) early experiments on social influence showed that when judging how far a point of light had moved, people thought they were not influenced by others when in fact they were (see also Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008). This interest in perception and reality continues to the present day with work showing that people underestimate their influence on others (Bohns & Flynn, 2013). Here, we consider how people's perceptions of how to improve accuracy by using advice compare with the reality of what actually increases accuracy.…”
Section: Perception and Reality In Using Advicementioning
confidence: 99%